Exploration with a Computer-Assisted Occupational Guidance Program - Impellitteri, Joseph T.; American Educational Research Association, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This paper describes an exploratory project of computer-assisted occupational guidance used with junior-high school boys in Altoona, Pennsylvania. A student interacts with the computer system from a terminal composed of a typewriter-input and readout device, a tape recorder, and a slide projector. With information related to the students' abilities, preferences, and educational plans stored in the computer, the student chooses one of 40 occupations about which he would like more information. After a brief description, if he wants more information, the computer summarizes his compatibility with the job, plays a taped interview with a worker, projects on-the-job scenes, and types a longer description of the job. The student may inquire about any number of jobs. Reactions to equipment were generally positive, with typeouts seen as most helpful. Content material was seen as at least adequate, although interesting and very useful. Procedures were seen as satisfactory and desirable, although 49% of the boys indicated they missed the opportunity to discuss problems during their sessions with the computer. (BP)
ERIC Note: Paper presented at the annual meeting of the American Educational Research Association, Los Angeles, California, February 5-8, 1969.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Guidance Programs; Information Services; Information Sources; Junior High School Students; Career Guidance; Computers; Information Dissemination; Occupational Information